Mitos Eksploitasi Tubuh Pada Seni Instalasi Dalam Film Penyalin Cahaya - Nabila Landiana Nugroho; Suprihatin (DIGICOM : Jurnal Komunikasi dan Media, 2022)
A Movie that deals with social issues in the community open up new knowledge from the storyline line that feeds the movie's researchers and directors, especially as a mass communication medium that can provide a spectacle so easily. One of the movie on social issues was that of transcribing light. Light copyists discuss sexual harassment that often occurs in public domains, particularly in the field of education. The elaborately researched problem is to find the myth that the text producers in the light-prescribing film. Researchers use a descriptive qualitative method of research with the semiotics of Roland Barthes. Further analysis of the data is made by documenting observations of each scene relating to sexual harassment behavior that is linked to the literature that researchers obtain. In this regard, researchers have discovered a myth that wakes up in the array of several carefully studied scenes - the myth of the exploitation of the body in installation art. The behavior of this body exploitation is sexual abuse without physical touch because the perpetrator only uses part of the victim's body as an inspiration for the installation. Thus, it may be desolated to the film that has given the public a new insight into the motives of the now prevalent cases of sexual abuse without.